Police organization in the Republic of Croatia – problems in decision making - Kovacicek, Kresimir (Applied Studies in Agribusiness and Commerce, 2008)
During the last few years of my police work I had a chance to speak and share opinion with my work associates about the police system in Croatia. My colleagues sometimes shared my opinion and sometimes they did not about the quality of police organization. Everyone’s conclusion was that some sort of change in the police organization has to be made; organization of the police must follow and embrace modern standards in organization and conduct. Almost each person had the same opinion about police management and decision making. Their opinion was that management is not efficient; decision making is based on chain of command and not on finding good solutions; members of the management team do not have education or creativity to be qualified managers; form is more important than the quality of work.